Producción, estabilización y evaluación de la enzima retrotranscriptasa recombinante obtenida a partir de Escherichia coli BL21(DE3) (2024)
Molecular tests represent a key tool in the diagnosis of various diseases, particularly those of infectious origin. During the pandemic, these tests became the cornerstone of diagnosis due to their versatility, speed, specificity, and sensitivity, as they allowed for the implementation of timely treatments and epidemiological containment measures. The RT - qPCR technique enabled the detection of the SARS - CoV - 2 virus; however, the overwhelming demand for these tests generated a shortage of critical supplies, particularly the MMVL - RT enzyme, essential for performing the technique. Therefore, in response to this scarcity and with the aim of ensuring a local supply of reverse transcriptase, Icesi University has proposed a comprehensive methodology for its obtention and storage. This methodology covers the production, stabilization, and evaluation of recombinant RT enzyme obtained in - house from Escherichia coli BL21(DE3). The work sequence includes the expression of the MMLV - RT enzyme in E. coli BL21(DE3) bacteria, followed by its purification through affinity chromatography using a histidine tag. Furthermore, the formulation of the enzyme in a storage buffer and the qualitative evaluation of enzymatic activity allowed for a comprehensive assessment of the quality attributes of the enzyme stored for one month. The result obtained was an enzyme with a high degree of purity, specific and functional, retaining its activity even after one month of storage at temperatures of 4ºC and - 20ºC.